Riverine fruit Dacryodes rostrata crude oil as a potential dietary lipid source for Malaysian mahseer, Tor tambroides - Bami, Mahkameh Lashkarizadeh; Kamarudin, Mohd Salleh; Saad, Che Roos; Arshad, Aziz; Ebrahimi, Mahdi (Universiti Putra Malaysia Press, 2018)
Riverine fruits, including lipid-rich Dacryodes rostrata, are commonly consumed by the omnivorous Malaysian mahseer (Tor tambroides) and other tropical riverine cyprinids in their natural habitats. To increase its aquaculture production, feeding the fish with an optimized diet that meets all its nutritional requirements is of crucial importance. This study was performed to investigate the effects of varying levels of D. rostrata oil on the growth performance, body composition and fatty acid profile of juvenile Malaysian mahseer. Juveniles (1.81 g ± 0.11) were fed the test diets (0, 1.25, 2.5, 3.75 and 5% D. rostrata oil) for 12 weeks in triplicated groups. Crude palm oil (CPO) was used as the control. Fish given 0% D. rostrata oil showed the greater growth performance, while juveniles fed 2.5% D. rostrata oil demonstrated the highest muscular retention of long-chain polyunsaturated fatty acids (both n-3 and n-6 PUFAs), which have beneficial health effects for human consumers. From the results, it was suggested that T. tambroides juveniles be fed with 5% CPO for the grow-out period. A finishing diet containing 2.5% D. rostrata oil was suggested for the fish towards the end of its culture period to achieve the highest concentration of long-chain PUFAs (both n-3 and n-6) in the muscle tissue, which is an important criteria for the health of humans as fish consumers.